Feeding of bakery products as replacement of cereal grains alter fecal microbiome and improve feed efficiency in fattening pigs - Hartinger, Kristina; Vötterl, Julia C.; Koger, Simone; Klinsoda, Jutamat; Sharma, Suchitra; Verhovsek, Doris; Metzler-Zebeli, Barbara U. (Frontiers in Sustainable Food Systems, 2024)
The re-integration of former foodstuffs, such as bakery products (BP), into pig feed reduces the feed-food competition and increases the sustainability of pig production. Nevertheless, there are concerns about the altered fatty acid profile in BP compared to standard diets and their effects on meat quality and the intestinal microbiome. The present study investigated the effects of replacing 30% cereal grains with BP in the diet on performance, microbiome composition and metabolites in feces of fattening pigs, economic aspects and meat quality characteristics. A total of 132 pigs (Large White × Piétrain; 11 weeks of age) were fed two diets containing 0 or 30% BP until reaching slaughter weight in three replicate batches. Fecal samples were collected for 16S rRNA amplicon sequencing after 6 weeks, whereas body fat samples were collected after 9 weeks on the diet. The results showed that BP can replace cereals in pig diets by up to 30% without impairing animal performance, while improving feed efficiency and reducing feed costs by 9% compared to the control. Additionally, pigs fed the BP diet had a 50%-higher n-3 fatty acid content in the neck and abdominal fat compared to the control. The improved feed efficiency in BP-fed pigs may be related to positive effects on the fecal microbiome, such as a higher alpha diversity and a reduction of fungi and yeasts. Our study provides valuable insights into the benefits of including BP in diets of fattening pigs, which should be investigated in future studies on other BP types.